Det Gamle Testamentes kanoniske status: Omkring Notger Slenczka, Vom Alten Testament und vom Neuen. Beiträge zur Neuvermessung ihres Verhältnisses - Müller, Mogens (Dansk Teologisk Tidsskrift, 2019)
Taking departure in the invitation in Slenczkas new book to discuss the role of the Jewish Holy Scriptures in a Christian canon, this article starts with contesting the validity of the arguments for introducing Old Testament readings in the service of the Danish Church. Reading the Old Testament in the light of Christian faith as if it in reality is about Christ was no longer possible after Enlightenment. With a historical and critical study, it became clear, that the Old Testament was Jewish and not Christian Scripture. In continuation of some deliberations in Luther, and especially the thoughts of F. Schleiermacher, A. von Harnack and R. Bultmann, Slenczka argues, that we today need to draw the consequence of this view. It was only in the reception of the Church that the Old Testament became a Christian text, and this cannot be ascribed a retroactive effect, a Jewish understanding and reception being much more appropriate. Its meaning in a Christian Bible, therefore, can only be to witness about man’s place towards God without Christ. From this follows that in a Christian Bible the Old Testament cannot figure with the same degree of canonicity as the New, instead it should be reckoned at the same level as the Old Testament Apocrypha.